Everything you need to know about stress - Ayer, Eleanor H. (New York : Rosen Pub. Group, 1998)
Explains what kinds of events cause stress, the effects of stress, and how to manage it.
Includes bibliographical references (p. 62) and index.
5.9
Young Adult
Keywords: Stress (Psychology) -- Juvenile literature; Stress management -- Juvenile literature; Stress (Psychology); Stress management; Stress (Psychology)